2011
DOI: 10.1242/jeb.057877
|View full text |Cite
|
Sign up to set email alerts
|

Daily torpor reduces mass and changes stress and power output of soleus and EDL muscles in the Djungarian hamster, Phodopus sungorus

Abstract: SUMMARYDjungarian hamsters (Phodopus sungorus) undergo bouts of daily torpor in response to reduced photoperiod. Metabolic rate, body temperature and energy cost are reduced during torpor. The present study exposed Djungarian hamsters to two different photoperiod regimes at a room temperature of 19-21°C: long photoperiod (control, 16h:8h light:dark, N8) and short photoperiod (torpor, 8h:16h light:dark, N8). After 14weeks, muscle mechanics were analyzed in each group, examining both extensor digitorum lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Indeed, average muscle strength following hibernation is only reduced by 12.6% relative to pre-hibernation values. This trend holds for rodents (Cotton and Harlow, 2010;James et al, 2013James et al, , 2011, bats (Choi et al, 1998;Lee et al, 2008) and bears (Harlow et al, 2001;Hershey et al, 2008;Lohuis et al, 2007b) (Table 1). Furthermore, these studies show minor changes in contraction time (2.2% less than pre-hibernation values) and relaxation time (1% more than pre-hibernation values) that are generally in agreement with changes in muscle mass, protein and fiber-type ratios.…”
Section: Skeletal Muscle Contractile Performance During Hibernationmentioning
confidence: 83%
See 2 more Smart Citations
“…Indeed, average muscle strength following hibernation is only reduced by 12.6% relative to pre-hibernation values. This trend holds for rodents (Cotton and Harlow, 2010;James et al, 2013James et al, , 2011, bats (Choi et al, 1998;Lee et al, 2008) and bears (Harlow et al, 2001;Hershey et al, 2008;Lohuis et al, 2007b) (Table 1). Furthermore, these studies show minor changes in contraction time (2.2% less than pre-hibernation values) and relaxation time (1% more than pre-hibernation values) that are generally in agreement with changes in muscle mass, protein and fiber-type ratios.…”
Section: Skeletal Muscle Contractile Performance During Hibernationmentioning
confidence: 83%
“…The majority of studies conducted on hamsters (Deveci and Egginton, 2002b;James et al, 2011), ground squirrels (Cotton and Harlow, 2010;Gao et al, 2012;James et al, 2013;Nowell et al, 2011;Steffen et al, 1991;Yang et al, 2014) and bats (Kim et al, 2000;Lee et al, 2008;Yacoe, 1983a) have shown relatively minor changes in muscle mass and protein content during hibernation, with most reporting 5-30% decreases in mass and 5-15% decreases in protein (Table 1). There is, however, some variation depending on species, specific muscles and sampling period.…”
Section: Morphological Changes During Hibernationmentioning
confidence: 99%
See 1 more Smart Citation
“…This applies to many species, such as bears, squirrels, woodchucks, bats, hamsters, prairie dogs and marmots (Cotton, 2016;Cotton and Harlow, 2010;Doherty et al, 2012;James et al, 2011;McGee-Lawrence et al, 2015Utz et al, 2009;Wojda et al, 2012). However, some small hibernators, such as the 13-lined ground squirrel (Ictidomys tridecemlineatus) have been reported to exhibit microstructural bone loss (osteocytic osteolysis) during hibernation bouts, which has not been observed in larger hibernating animals (McGeeLawrence et al, 2011).…”
Section: Maintenance Of Musculoskeletal Properties In Hibernators Andmentioning
confidence: 99%
“…James and co-workers demonstrated that daily torpor in the Djungarian hamster actually increased isometric force and work loop power output in soleus muscle but had no effect on either soleus or extensor digitorum longus (EDL) work loop fatigue resistance (James et al, 2011). However, the Djungarian hamster spends only a few hours each day in torpor, while most hibernators undergo much longer torpor bouts that could cause more significant changes in contractile performance that might not have been detected via the use of isometric methods in all other previous studies on hibernators.…”
Section: Introductionmentioning
confidence: 99%